The normal growth of the common iliac arteries in human fetuses – an anatomical, digital and statistical study - Szpinda, Michał (International Scientific Literature, Inc., 2012)
BACKGROUND: The present study was carried out to compile normative data for dimensions of the common iliac arteries at varying gestational ages. MATERIAL/METHODS: We used anatomical dissection, digital-image analysis (system of Leica QWin Pro 16) and statistical analysis (Student T test, one-way ANOVA, post-hoc RIR Tukey test, and regression analysis) to examine the increase in length (mm), proximal external diameter (mm), and volume (mm(3)) of the common iliac arteries in 124 (60 males, 64 females) spontaneously aborted human fetuses aged 15–34 weeks. RESULTS: Neither sex nor right-left significant differences were found (P>0.05). The length ranged from 4.76±1.05 to 15.38±1.60 mm on the right, and from 4.92±1.33 to 14.91±1.25 mm on the left, according to the linear functions y=−3.598+0.585×Age ±1.522 (R(2)=0.83) and y=−3.107+0.554×Age ±1.444 (R(2)=0.83). The proximal external diameter increased from 0.66±0.19 to 2.30±0.42 mm on the right, and from 0.66±0.14 to 2.16±0.42 mm on the left, according to the quadratic models y=1.392−0.110×Age+0.004×Age(2) ±0.285 (R(2)=0.77) and y=1.283−0.099×Age+0.004×Age(2) ±0.238 (R(2)=0.81). The volumes were increasing from 1.93±1.74 to 66.95±29.31 mm(3) on the right, and from 1.91±1.65 to 56.86±25.17 mm(3) on the left, given by the quadratic functions: y=99.69−10.60×Age+0.287×Age(2) ±14.40 (R(2)=0.67) and y=82.62−8.86×Age+0.242×Age(2) ±11.60 (R(2)=0.71). CONCLUSIONS: The common iliac arteries grow linearly in length, and parabolically in both diameter and volume. The right common iliac artery constitutes a predominant vessel in relation to its length, external diameter and volume. The morphometric data on the common iliac arteries may serve as a useful reference in the prenatal diagnosis and monitoring of congenital aorto-iliac abnormalities.